Building a personalized patient education model for general practice by Delphi method. (9th July 2022) - Li, Jie; Xu, Mu; Jiang, Yue
Abstract: Background: As one of the 3 strategic measures for disease prevention and control in the 21st century identified by WHO, patient education is the most effective measure to change people's behaviour and lifestyle. However, there are many problems with patient education in general practice in China. Because there is no suitable and uniform mode of patient education for the busy and crowded Chinese general practice. Therefore, it is necessary to establish an appropriate personalized patient education model. Methods: There were 3 rounds of consultation of the Delphi method. Each round of consultation is adjusted, modified, or deleted based on the previous round according to the degree of concentration and coordination of expert opinions. Thus form the index system of personalized patient education model. Using Cronbach α to conduct an internal consistency test for the index system. Results: Twenty-three participants participated in the study. The effective recovery rate of consultation was 100%. In the third round of consultation, the variation importance coefficient was 0–0.25, the variation operability coefficient was 0.07–0.26. Kendall's W of importance and operability score was significant (Kendall's W = 0.186; P < 0.01). The chi-square test result of importance is ( X 2 = 232.744) and operability is ( X 2 = 246.156). The Cronbach α was 0.974. EFA (exploratory factor analysis) indicates the model has good construct validity. Conclusions: The CAPDCA personalized patient education model was preliminarily constructed in this study. Specifically, 6 first-level indicators including collection (C), assessment (A), plan (P), do (D), check (C), aggrandizement (A), 24 second-level indicators, and 34 third-level indicators. That forms the cyclic personalized patient education paradigm which has reasonable structure and high feasibility.